A transformação da lagarta - Colosso, Cristiane Otília; Lima , Eliene Xavier de; Bento , Miriam Furtado; Schiavinato , Ricardo Leandro; Gonçalves, Zélia Barbosa (REVISTA PROGRAMA A UNIÃO FAZ A VIDA_____________________________________________________________________________________________________________, 2021)
>>> ver pdf